Shortcomings in the Personal Sphere of Companies and their Conditions - Gableta, Małgorzata; Bodak, Andrzej (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Legislative action undertaken in the European Union in the field of employee rights protection is a reaction to problems disclosed in the personal sphere of companies. Implementation of guidelines of the EU law should persuade Polish employers to increase their interest in that sphere, in relation to requirements formulated by relevant directives and ordinances. The presented empirical research results disclose the shortcomings that still occur in the study sphere in terms of implementation of EU guidelines.